PALLIATIVE TREATMENT OF MALIGNANT GASTRIC OUTLET OBSTRUCTION WITH SELF EXPANDABLE METAL STENTS - Khan, Hashmatullah; Zhining, Fan; Ghafoor, Aamer; Khattak, Abbas Khan; Hassan, Muhammad Kamran (Journal of Postgraduate Medical Institute, 2016)
Objectives: To determine the technical feasibility and clinical outcome of Self-expandable metal stents (SEMS) to palliate symptoms of malignant gastric outlet obstruction (GOO). Methodology: This was a prospective non-randomized study. It was performed at Jiangsu Province Hospital, Najing China. Duration was one year from april 2015 to 2016. Patients with gastric outlet obstruction caused by unresectable malignancy of stomach, pancreas and duodenum were included in a consecutive manner. Stenting was done under direct endoscopic and fluroscopic visualization and conscious sedation. Only uncovered SEMS were used. We evaluated our technical success rate, Gastric Outlet Obstruction Scoring System (GOOSS) score before and after stent placement, and complications. Results: Total number of patients was 30. Self Expandable Metal Stents (SEMS) were successfully placed in all patients. Thus, technical success rate was100%. 29 patients resumed oral intake without vomiting. Clinical success rate was 96.7%. There was significant improvement in GOOSS score with stenting (p value<0.05). Only 2 (6.7%) patients had their stents blocked due to tumor ingrowth later in the course of follow-up which was successfully managed by re-stenting. Conclusion: Use of SEMS as a palliative modality for malignant GOO is a feasible, safe and effective method.